An Analysis of Morphological Errors in Arabic Thesis Abstracts at a University Level - Fuad Hasim, Muhamad; Muflihah, Muflihah; Baihaqi, M.; Iqbal Fuadhi, Muhammad; Islamiyah, Nur (Nurul Jadid University, 2025)
Morphological competence plays a crucial role in producing academically sound Arabic writing, especially for non-native learners in higher education. This study aims to analyze and categorize morphological errors found in the thesis abstracts of students in the Arabic Language Education Study Program at IAIN Kediri. Using a qualitative descriptive method with a content analysis approach, the research focuses on identifying dominant patterns of morphological mistakes and offering strategic insights to improve linguistic accuracy in students’ final academic projects. The data consisted of three randomly selected abstracts from 2023–2024 graduates, which served as the primary source, supported by secondary sources such as books and articles related to Arabic morphology. The analysis process involved four stages: data collection, error identification, explanation, and evaluation. The results revealed four major categories of morphological errors: incorrect word formation, misapplication of wazan (word patterns), inaccurate use of various types of hamzah, and improper placement of ḍamīr (pronouns). These findings suggest the need for targeted instructional interventions to reinforce students’ understanding of Arabic morphological structures in academic contexts.